Probability distribution and recommended values of passenger car external dimensions in mechanical parking garage design - Jingshu Zhang; Hongbo Yang; Zhuo Chen; Ting Yu; Haiyang Liu (Journal of Asian Architecture and Building Engineering, 2022)
In order to determine the external dimensions of passenger car, to meet the current parking needs when designing a mechanical parking garage. In this study, 7193 groups of external dimensions and sales volume data of passenger car in the Chinese market from 2009 to 2020 are collected. Then, appropriate probability distributions are used to fit the collected data. Combined with their actual market share, the recommended external dimensions of sedan, SUV and MPV, separately, as well as all of them together, defined as general vehicles, are given by using probability statistics method. It is concluded that the external dimensions of sedan and SUV obey the t Location-Scale distribution, while MPV follows the mixed normal distribution. The length and width of general vehicles follow the t Location-Scale distribution and the height obeys the mixed normal distribution. The length, width and height of sedan are 5100 mm, 1890 mm and 1560 mm, respectively. The ones of SUV are 4950 mm, 1940 mm and 1850 mm, respectively, and for MPV they are 5300 mm, 1900 mm and 2000 mm, respectively. The corresponding dimensions of the general vehicles are 5150 mm, 1930 mm and 1900 mm, respectively. The proposed passenger car external dimensions can provide guidance for the garage design, aiming at the optimum space exploitation.